(untitled) (Journal of Educational Sciences, 2024)
Introductory speech on the research topic: the article examines the organization, structure, content of the system of preparing future teachers-psychologists for Career Guidance work with students in accordance with the conditions of digitalization of education and the need for their interaction with innovative processes in education. The educational process of the Higher School should increase the readiness of future teachers-psychologists for professional orientation work with students, create the most favorable conditions for them to acquire the knowledge and skills necessary for the formation of students ’ self-esteem, self-knowledge, professional self-determination, develop their abilities, and adapt vocational guidance to the conditions of digitalization. The purpose, main directions and ideas of scientific research. The purpose of the study is a scientific theoretical and methodological justification of the preparation of future teachers-psychologists for professional orientation of students in the context of digitalization of Education. The article clarifies the essence of the concepts of professional orientation, professional self-determination of students, training of future teachers-psychologists, professional training. Brief description of the scientific and practical significance of the work. The scientific and practical significance of the work is the problem of methodically increasing the readiness of future teachers-psychologists for Career Guidance work, updating the content of Career Guidance work in the context of digitalization of knowledge and the effective use of the capabilities of digital technologies. Brief description of the research methodology. A scientific theoretical analysis of the works of domestic and foreign scientists was carried out, which considered the issue of preparing future teachers-psychologists for professional orientation of students. In order to determine the views of high school students on the state and approaches to the implementation of modern career guidance work, they were surveyed. The degree of understanding of the importance of vocational guidance work for students by future teachers-psychologists, modern relevant technologies of implementation is studied. The main results and analyzes of the research work, conclusions. Based on the results of the survey obtained on the topic of the study, the authors put forward the problem of improving the content of Career Guidance work through the rational use of the capabilities of digital technology. The value of the study (the contribution of this work to the relevant field of knowledge). It was noted that the web site is being developed as an auxiliary tool for future teachers-psychologists in the professional orientation of students, and it is planned to improve the content of Career Guidance work through other possibilities of digital technology. Practical significance of the results of work. The result of the research problem is the implementation of forms, methods and means of professional orientation in accordance with the conditions of digitalization of Education. Keywords: digitalization of education, teacher-psychologist, career guidance, professional self-determination, training, professional training, competence, digital technologies.